Increasing Health Burdens Driven by Global Trade Induced Air Pollution - Ruifei Li; Yu Luo; Xu Zhu; Jin Zhang; Pei Hua; Zhenyu Wang; Wenyu Yang; Qiuwen Chen; Hui Li (Earth's Future)
Abstract Globalization has led to an increasing geographical separation of primary input, consumption and production, and consequently to a substantial transboundary transfer of air pollution and associated health burdens through international trade. Here, we develop an integrated framework to determine the consumption‐ and income‐based global atmospheric emissions, and quantify the drivers of associated health impacts from 2000 to 2015, and evaluate the impacts of international trade on PM2.5‐related deaths by hypothetical scenarios. Results show that consumption transferred more primary PM2.5 emissions (2.2 Mt, 23.5%) and caused more additional mortality (241,000 deaths) through international trade than primary input (emission: 1.1 Mt, 12.3%, mortality: 167,000 deaths) in 2015. Top three key sectors contributed to more than half of emission flow driven by consumption (commercial, construction, electrical and machinery) and primary inputs (commercial, petroleum, and mining). Health benefits of reduced emissions intensity, which avoided 1.4 million deaths, were largely offset by not only increases in consumption and primary input levels but also population vulnerability, resulting in the increase in mortality (0.8 million) from 2000 to 2015. Changes in primary input (1.2 million deaths) contributed more to the rise in health burdens than changes in consumption (1.0 million deaths). Hypothetical scenarios show that the participation of Western Europe in international trade contributed to the reduction in global health burden, while the USA gained health benefits from international trade. Accordingly, our findings provide profound suggestions for future policy decisions from different perspectives and demonstrate that optimizing global supply chain through cooperation would mitigate the PM2.5‐related health impacts.